Reevaluating Sail Propulsion for Traditional Fishing Vessels: Economic and Environmental Benefits of The 'Ijon-Ijon' Boat in Lamongan, East Java (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2025)
This study aimed to evaluate the techno-economic feasibility of reintroducing sail propulsion on the traditional "Ijon-Ijon" fishing boat in Lamongan, East Java. The methodology involved numerical calculations and ship modeling to determine vessel resistance and sail-generated thrust. A 76 m² triangular sail was designed and analysed using established aerodynamic principles. The results showed that the sail generated a thrust of 85.6 N, 135 N, and 323 N at wind speeds of 4 m/s, 5 m/s, and 8.245 m/s (16 knots), respectively, enabling the vessel to achieve speeds exceeding 4.5 knots in good wind conditions. The economic analysis projects monthly fuel cost savings of IDR 1,315,800 at 16 knots and IDR 2,652,000 at 30 knots. In conclusion, reintroducing sail propulsion is a viable strategy for reducing operational costs and enhancing sustainability in Indonesia's traditional fisheries sector.